Fatal Direct Current Electrocution in a Welder. (December 2020) - Hans, Anmol; Key, Phillip; Prahlow, Joseph A.
Abstract : Abstract: Direct current (DC) electrocution is exceedingly rare, especially in the context of workplace accidents and exposure, where electrical fatality is almost exclusively associated with alternating current (AC). The DC electrocution requires a much higher voltage to cause significant injury and death, and therefore is generally considered safer than AC. Here, we present a case of DC electrocution where a welder accidentally electrocuted himself while repairing a metal plate inside a silo. The decedent had complained of feeling shocks in his arm while welding twice before being electrocuted. Autopsy revealed minimal trauma, along with a classic targetoid electrical burn and punctate lesions likely to be electrical burns. Correlation of the history obtained at the scene and the examination performed at autopsy aided the identification of this rare cause of death.